A contribuição da formação continuada para os professores da educação infantil da Instituição Adventista do Paraná: Regional Norte - Balbé, Marta Maria Gonçalves (2011)
This research aims to understand how the process of continuing education, which happens within schools, contributes to the personal and professional lives of teachers. The approach that has been adopted is anchored in qualitative studies. The theoretical studies of Flick (2009) and Gamboa (2007) guided the planning of the research with regard to the method and procedures for collecting and analyzing empirical data. The instrument set for data collection was narrative interviews with ten teachers working in early childhood education classes at a private religious institution in Maringá, in southern Brazil. Two issues guided this research: What are the contributions that initial training and continuing education brought to your personal and professional life and your pedagogical practice? The other issue asked the teachers to report the conflicts, frustrations and hopes that are present in their daily personal and professional life. The works of authors such as Cunha (1998, 1996), Demo (1999), Duarte (1998) Enguita (1989, 1993), Garcia (1999), Hargreaves (2004), Kreutz (1996), Magnani (1993), Mello (1992), Nóvoa (1992) and Apple (2000) were the basis for discussions about initial training and continuing educator. The authors Heywood (2004), Kramer (1995, 2006), Kuhlmann (2007), Postman (1999) and Sarmento (2001) contributed to the understanding of childhood as a generational category and the history of early childhood institutions. The results of this research show that teachers recognize the importance of initial training however, in their narrative discourses they point out that graduation alone is insufficient to meet the complex demands that emerge from the daily school routine. The teachers also recognize that continuing education is an important process that brings theory and practice into the context of teacher training. They similarly recognized that such training, which occurs in service, goes beyond merely equipping a teacher for teaching practice. This study finds that continuing education is a fundamental process, recognizing the opposing and complementary dimensions of theory and practice without losing sight of the entire educational process